Psikologi Cerai Gugat di Kabupaten Tulungagung - Widyarto, Wikan Galuh; Arifuddin, Alfan (Universitas Nusantara PGRI Kediri, 2023)
This study intends to examine the significance of the motivations underlying the incidence of contested divorce, the factors contributing to the occurrence of contested divorce, and the feelings associated with contested divorce In Tulungagung Regency. The research subjects, i.e., the defendants in the litigation the researcher researched, were analyzed using a qualitative research methodology and a phenomenological model. Choosing research participants based on data gathered through interviews, observations, and life experiences using the snowball sampling technique (self-report). Data reduction, presentation, verification, and decision-making techniques were used in the analysis of the data, while tests for the data's dependability, trustworthiness, and certainty were used to ascertain its validity. The study's conclusions suggest that the motivation to have a divorce is driven by the needs for survival, security, affection, self-esteem, and self-actualization. Economic difficulties, carelessness (neglect/neglect), domestic violence treatment, family system support, poor behavior (drinking, returning home at night without a good cause), and a lack of knowledge and marriage preparedness were among the factors identified. Pre-divorce (a time of conflict), divorce process (mediation/divorce decision), and post-divorce are the three periods into which emotions are divided in accordance with the current divorce process.